Answer:
its A
Step-by-step explanation:
Trust me
How unspecific? What's the cost of one
Answer:
* = b²
Step-by-step explanation:
You know that the square of a binomial is of the form ...
(x + y)² = x² + 2xy + y²
Matching given terms, we have ...
49 = y²
2xy = 14b
Solving the first of these relations for y, we have
y = √49 = 7
Putting that in the second relation and solving for x, we find ...
2x·7 = 14b
14x = 14b
x = b
Then the first term of the expansion, x², will be b².
The missing term is b².
Answer:
i'm 100% sure its A
Step-by-step explanation: